2006
DOI: 10.1021/ja060035k
|View full text |Cite
|
Sign up to set email alerts
|

Layering at an Ionic Liquid−Vapor Interface:  A Molecular Dynamics Simulation Study of [bmim][PF6]

Abstract: The structure of the planar liquid-vapor interface of a room-temperature ionic liquid, 1-n-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF6]), is studied using atomistic molecular dynamics simulations. Layering of the ions at the interface is observed as oscillations in the corresponding number density profiles. These oscillations, however, are diminished in amplitude in the electron density profile, due to a near cancellation in the contributions from the anions and the cations. An enhancement by 12%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
214
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(250 citation statements)
references
References 45 publications
33
214
3
Order By: Relevance
“…Further, by having water interact with the C 2 À H group, the C 2 À H bond will point into the bulk liquid and the C 4 À H and C 5 ÀH bonds will be directed into the vapor phase. [14,94] Theoretical calculations have confirmed the interaction between water and ILs. À1 at B3LYP/6-31 + + G** level after BSSE correction.…”
Section: Dh ¼ à80ðnmentioning
confidence: 89%
“…Further, by having water interact with the C 2 À H group, the C 2 À H bond will point into the bulk liquid and the C 4 À H and C 5 ÀH bonds will be directed into the vapor phase. [14,94] Theoretical calculations have confirmed the interaction between water and ILs. À1 at B3LYP/6-31 + + G** level after BSSE correction.…”
Section: Dh ¼ à80ðnmentioning
confidence: 89%
“…Therefore, it is important to have a fundamental understanding about the characteristics of the confined ILs. Investigations of the interfaces of the ILs, both solid and liquid, have been carried out using both experimental and simulation studies [11][12][13][14][15][16][17][18]. Recently, structure of the electrical double layer in IL 1-butyl-3-methylimidazolium hexafluorophosphate [BMIM][PF 6 ] near a charged and uncharged graphite surface has been studied [19].…”
Section: Introductionmentioning
confidence: 99%
“…in Refs. [6][7][8][9][10][11][12][13][14][15] Most of the computational effort has been focused on alkylimidazolium cations in combination with halides, BF − 4 , PF − 6 , and NTf − 2 anions. All these studies found considerable layering at the interface with ions strongly aligned leading to enhanced packing.…”
Section: Introductionmentioning
confidence: 99%